Preserving Yellowstone's Natural Conditions Science and the Perception of Nature. - Pritchard, James A. (University of Nebraska Press, 2022)
In this new edition James A. Pritchard has added a summary of recent developments in wildlife science and management and discusses historical continuities in the role of Yellowstone Park as a wildlife refuge and conservator.